Comparative diversity of birds across habitat gradients in the Polilo Islands, Philippines - Gonzalez, Juan Carlos T., Ocampo, Pablo P. Jr. and Gruezo, William SM (Asia Life Sciences : the Asian International Journal of Life Sciences, 2010)
Ecological relationships of birds along habitat gradients in the Polilo Islands were determined using diversity and similarity indices derived from transect counts and netting results. Species richness and endemism was highest on both old growth and secondary forests, followed by agro-forests, coastal settlements and mangroves. Bird species diversity between habitats was highest for secondary forests and lowest for coastal settlements. Among islands, richness, diversity and endemism was highest on Polilo, followed by Patnanungan, Jomalig and Minasawa. Feeding guilds were equally represented in forest sites, but not in coastal sites with more waders. Diversity and endemism was inversely proportional to habitat disturbance, but increased with larger island size, elevation, forest cover and stratification. Similarity was highest between old growth and secondary forests, sharing intolerant forest birds. Lowland forests and coastal habitats showed least similarity. Polilo and Patnanungan islands had highest similarity, due to presence of lowland evergreen forests absent in other islands. Avifauna of Jomalig was more similar to Minasawa due to dominance of coastal vegetation. Similarity between habitats was based on ecotones and persistence of tolerant forest birds like Hypsipetes philippinus found in all habitats. Similarity between islands was influenced by dominant vegetation, rather than distance between islands. Habitat loss from extensive logging, mining and conversation to agriculture has detrimental effects on forest-dependent birds. Old growth lowland forest was restricted only to Polilo watershed, with unprotected remnant fragments of secondary forests and mangroves scattered in islands. Conservation efforts must focus on protecting residual forests and mangroves in all islands, and expand existing reserves through forests corridors.